2017
DOI: 10.1186/s12978-017-0430-2
|View full text |Cite
|
Sign up to set email alerts
|

Protected to death: systematic exclusion of pregnant women from Ebola virus disease trials

Abstract: BackgroundFor 30 years, women have sought equal opportunity to be included in trials so that drugs are equitably studied in women as well as men; regulatory guidelines have changed accordingly. Pregnant women, however, continue to be excluded from trials for non-obstetric conditions, though they have been included for trials of life-threatening diseases because prospects for maternal survival outweighed potential fetal risks. Ebola virus disease is a life-threatening infection without approved treatments or va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 64 publications
0
84
0
Order By: Relevance
“…12 Today, the inclusion of women in clinical trials is both expected and commonplace though usually requires that a subject be nonpregnant and/or compliant with effective contraception. 13 However, pregnant women remain habitually excluded from clinical pharmacologic/ therapeutic trials that do not address obstetric conditions. This is due, in large part, to potential risks of teratogenicity weighed against potential medical benefits to the mother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Today, the inclusion of women in clinical trials is both expected and commonplace though usually requires that a subject be nonpregnant and/or compliant with effective contraception. 13 However, pregnant women remain habitually excluded from clinical pharmacologic/ therapeutic trials that do not address obstetric conditions. This is due, in large part, to potential risks of teratogenicity weighed against potential medical benefits to the mother.…”
Section: Discussionmentioning
confidence: 99%
“…3 The HIV/AIDS epidemic serves as a singular and excellent example of inclusion of pregnant women in the earliest phases of drug development. 13 However, this was predominantly driven by the potential benefit of reduced vertical transmission to the fetus. 14 Unfortunately, the pattern of excluding pregnant women from clinical trials, even during epidemics, is not new.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women were excluded from receiving the vaccine in West Africa, as there was thought to be insufficient evidence of vaccine safety. This decision led to anger that women were being put at unnecessary risk because of their exclusion (73,90,91).…”
Section: The Ethics Of Enrolling Pregnant Women and Children In Reseamentioning
confidence: 99%
“…It is also the largest and most deadly of the ten Ebola outbreaks to occur in DRC [2], the country where Ebola was first identified during the 1976 Yambuku outbreak [3]. Throughout multiple outbreaks of EVD, the infection has had a significant case fatality rate (CFR) among all persons who became infected, but historically the mortality has been especially high among pregnant women, fetuses and infants (less than 1 year of age) [4][5][6][7]. Prior to the West African Ebola epidemic which began in Guinea in December 2013, it was generally believed that EVD occurring in a pregnant woman was close to being non-survivable.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the West African Ebola epidemic which began in Guinea in December 2013, it was generally believed that EVD occurring in a pregnant woman was close to being non-survivable. Previous Ebola outbreaks had demonstrated that from 75 to greater than 90 percent of infected pregnant women had died as a result of EVD [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%